Unveiling the relationship between quality of academic life and regional development. Issue 1 (2nd January 2020) - Pedro, E.; Leitão, J.; Alves, H.
ABSTRACT: The paper examines the still unexplored role played by quality of academic life (QAL) related to Higher Education Institution (HEIs) students in fostering regional development. The work aims to assess the nature of the relationship between satisfaction and the QAL of HEIs' students; and also to evaluate whether the QAL is associated with the regional development of the HEIs' surrounding areas. The objectives are to identify which areas of academic life influence QAL and what the aggregate effects associated with HEIs are, in terms of regional development. Based on a sample of 719 students from all Portuguese public HEIs, a two-step methodology is applied. Firstly, a selected specification of a structural model (SEM-PLS) is tested to evaluate the impact of administrative management, infrastructure, educational provision and social action on QAL; and secondly, a Two-Stage Least Squares regression analysis evaluates the impact of the HEIs on regional development (NUTSII) using the Synthetic Regional Development Index. The main results reveal a positive and significant relationship between service satisfaction and QAL and statistically negative influence of QAL on regional development, which raises important challenges in terms of future research efforts contrasting high versus low density regions of HEIs influence in the international context.